PENERAPAN VIRTUAL LABORATORY UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA DI MASA PANDEMI - Nimas Arumningtyas; Mohammad Budiyanto; Aris Rudi Purnomo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This study aimed to describe the improvement of students’ science process skills by using virtual laboratory media with guided inquiry learning model on Archimedes’ Principle. The method of this study was pre-experimental design with one group pretest posttest design as a research design. The subject in this study were 35 students of VIII J class in SMP Negeri 1 Surabaya. The methods of data collection were by giving a pretest before and posttest after learning to measure students’ science process skills and observation using observation sheet to measure learning in every phase. The data were analyzed using the paired t-test and the N-Gain. The results obtained through the paired t-test; significance value was (0.00) < 0.05 therefore showed that there was a significant effect of the treatment on the students’ science process skills. As for the N-Gain test result was 0.8 consider as high category and classical completeness also achieved with percentage of 80%. Based on the study that has been done, it can be conclude that virtual laboratory media with guided inquiry learning model can improve students’ science process skills in Archimedes’ Principle.